High stomal outputs following interactions between opioid and opioid-like derivatives with CYP inducers - Elizabeth SL Low; Katrina Tan; Darren Wong (Intestinal Failure)
Background: International guidelines for the management of high output stoma (HOS) commonly involve the use of opioids and opioid-like derivatives, such as loperamide, to mitigate the risk or impact of intestinal failure. However, these agents often have significant drug-drug interactions that may reduce the efficacy of anti-diarrheal pharmacotherapy and risk prolonged dependency on parenteral nutritional and intravenous fluid replacement, if unrecognized. Case report: Two cases of patients prescribed rifampicin for differing indications demonstrate persistent HOS despite traditional management strategies, including maximal doses of anti-diarrheal agents. Rifampicin, a known cytochrome P450 enzyme inducer, increases metabolism of both codeine and loperamide, resulting, in these cases to reduced drug efficacy and intestinal failure. Conclusion: Prescribers must be mindful of the potential drug-drug interactions when co-administering drugs inducing cytochrome P450 expression with opioids commonly used in HOS management. Given the risk of opioid inefficacy and increased stomal outputs, close monitoring and careful drug titration is advised.